ANALISIS GAYA BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPAS KELAS IV DI SD NEGERI GAJAHMUNGKUR 04 SEMARANG - Kustiyanti Dewi; Joko Sulianto; Fine Reffiane (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
It is known that students’ learning styles vary, and thus it is imperative of teachers to acknowledges the differences. The purpose of this study is to discover the students’ IPAS learning style. Learning style is one of the learning forms that is in accordance to students’ characteristics, and could be a reason for teachers to improve learning quality. Moreover, it is easier for students to motivate themselves to learn. The research uses qualitative method. The data collection uses interview, ovservation, and documentation. Data validity is done by technique and source triangulation. Data analysis process uses data gatheting, data reduction, data presentation, and conclusions. The result of the research shows that the learning style of SDN Gajahmungkur 04 Semarang students’ on IPAS learning consists of visual characteristic much as 47% which means the students can understand problems while reading and able to solve learning questions by writing; Auditorial learning stylemuch as 33% which means students are able to understand better while the teacher is reading them the questions, able to know how to convey information gathered from the works orally, also able to understand the materials that is being presented orally; and kinesthetic learning style much as 20%, which means students prefer to solve problems in group, discuss, and not able to concentrate for a long period of time while sitting down. The result of the study shows that the learning style of the students of Grade IV SDN Gajahmungkur 04 Semarang consist of visual, auditory, kinesthetic, learning style, with the visual learning style as the most dominant among the rest.